Relationship of Lipid Profile with Wagner Severity Level in Diabetic Feet at General Hospital Dr. M. Djamil Padang - Ario, Yunes; Raflis Rustam; Vendry Rivaldi (Fakultas Kedokteran Universitas Sriwijaya (Faculty of Medicine, Universitas Sriwijaya) Indonesia, 2021)
A B S T R A C TIntroduction Diabetic foot is an erosion or injury to the epidermis or the distal soleof the foot and the base of the foot in people with diabetes mellitus (DM). Diabeticfoot is a major cause of limb amputation in non-traumatic cases. Per year, as manyas 2-3% of people with diabetes experience complications of diabetic foot. Theprevalence of DM sufferers with diabetic foot is 20-40% in developing countries. InIndonesia, the prevalence of DM sufferers with diabetic foot is around 15% with 32%mortality rate. One factor plays an important role in predisposing the occurrence ofdiabetic foot is the lipid profile. The aim of this study was to determine the correlationbetween lipid profile and Wagner Severity Level on diabetic foot patients at Dr. M.Djamil Central Public Hospital, Padang in the period of July 2020 to December 2020.Method: This research is an observational analytic study with cross sectionalanalytic design. The research sample of 47 cases was taken by non-probabilitysampling with the consecutive sampling method. This research is an observationalanalytic study with cross sectional analytic design. The research sample of 47 caseswas taken by non-probability sampling with the consecutive sampling method.Result: There were 47 cases that met the inclusion criteria where the 51-60 yearsage group (55.3%) was the largest group in cases of diabetic foot. Of these groups, itwas dominated by female patients, namely 31 patients (66.0%). Meanwhile, the BodyMass Index (BMI) was dominated by the group with BMI <25 kg/m2 with a total of26 patients (55.3%). Diabetic foot patient at Dr. M Djamil Central Public HospitalPadang who underwent amputation was 25 patients (53.2%) where most of them,namely 40 patients (85.1%) had suffered from Diabetes Mellitus for> 5-10 years. Thefindings obtained based on the Wagner Severity Level were that the Wagner grade 3-5 (heavy) group consisted of 24 people (51.1%) and Wagner 1-2 (mild) as many as 23people (48.9%). The results of the bivariate test between lipid profile levels withWagner Severity Level in diabetic foot patients showed a significant correlation asindicated by a p value <0.05. Conclusion: Wagner Severity Level which is gettinghigher in diabetic foot patients shows low HDL levels, high LDL levels and high levelsof triglycerides in blood plasma.